IMPLEMENTASI KEBIJAKAN PENYELENGGARAAN KOTA LAYAK ANAK DI KOTA DEPOK (STUDI KASUS PENANGANAN ANAK JALANAN) - Raina Rosyidah, (2022)
This study aims to analyze the Implementation of Child Friendly City Policy in Depok City (a case study of handling street children). The local government together with the Social Services work together in running the program directly from the Ministry of Women's Empowerment and Child Protection. This type of research is descriptive qualitative. This type of research uses a case study approach. Data sources in this study are primary data and secondary data. Data collection techniques used in this study are observation, documentation and interviews. Data Analysis Techniques used in this study using interactive analysis which includes three components: (1) data reduction, (2) data presentation, (3) drawing conclusions. The analysis of this model has three components that are well intertwined, namely before, during and after the implementation of data collection. This research involved 5 informants, namely the Head of Social Rehabilitation, Master School Trustees, NGO The Prakarsa and 2 street children. The results of the study show that the implementation of child-friendly city policies in the city of Depok has been running but still encounters obstacles in its implementation. The supporting factors for the implementation of the Child Friendly City Policy in Depok City in dealing with street children are the existence of a Child Friendly City Regulation No. 15 of 2013 concerning the Implementation of Child Friendly Cities in Depok City. In the implementation, Depok City has established cooperation between SKPDs. The inhibiting factors in its implementation are the lack of cooperation with the community and inadequate facilities to support the handling of street children.